Migraine aura-like symptoms at onset of stroke and stroke-like symptoms in migraine with aura - Scutelnic, Adrian; Kreis, Lukas A.; Beyeler, Morin; Heldner, Mirjam R.; Meinel, Thomas R.; Kaesmacher, Johannes; Hakim, Arsany; Arnold, Marcel; Fischer, Urs; Mattle, Heinrich P.; Schankin, Christoph J.; Jung, Simon (Frontiers in Neurology, 2022)
Background and Objectives: In general, suddenly occurring neurologic deficits, i.e. negative neurologic symptoms, are considered symptoms of focal cerebral ischemia, while positive irritative symptoms with gradual onset are viewed as characteristics of migraine aura. Nevertheless, cortical spreading depolarization, the pathophysiological basis of migraine aura, has also been observed in acute ischemic stroke. The aim of our study was to determine the frequency of migraine aura-like symptoms at ischemic stroke onset and stroke-like symptoms in migraine with aura. Methods: We interviewed 350 consecutive patients with ischemic stroke and 343 with migraine with aura using a structured questionnaire. Stroke diagnosis was confirmed by imaging and migraine with aura was diagnosed according to the current criteria of the International Headache Society. Patients with wake-up strokes or severe cognitive deficits that precluded a useful interview were excluded from the study. Results: Seventy-eight stroke patients (22.3%) reported visual symptoms, 145 (41.4%) sensory symptoms, 197 (56.3%) a paresis and 201 patients (57.4%) more than one symptom, compared to 326 migraine with aura patients (95%) with visual symptoms (p < 0.001), 175 (51%) with sensory symptoms (p = 0.011), 50 (14.6%) with paresis (p < 0.001) and 211 (61.5%) with more than one symptom (p = 0.27). Among stroke patients, migraine-like symptoms were frequent: 36 patients (46.2%) with visual disturbance and 78 (53.8%) with sensory symptoms experienced irritative sensations. Paresis-onset in stroke lasted longer than 5 minutes in 43 patients (21.8%). Spreading of sensory and motor symptoms occurred in 37 (25.5%) and 37 (18.8%) patients, respectively. Stroke-like negative symptoms in migraine with aura occurred in 39 patients (12%) with visual symptoms, in 55 (31.4%) with sensory symptoms, and paresis appeared suddenly in 14 patients (28%). More than one symptom in succession occurred in 117 stroke (58.2%) and in 201 migraine with aura patients (95.3%; p < 0.001). Conclusion: Many stroke patients experience migraine-like symptoms at stroke onset and many migraine with aura patients stroke-like symptoms. Though overall the symptom frequencies of the two groups are significantly different, to clarify the differential diagnosis in an individual patient requires additional history elements, physical findings or results of ancillary investigations.